2021
DOI: 10.3390/ijms22179394
|View full text |Cite
|
Sign up to set email alerts
|

Links between Infections, Lung Cancer, and the Immune System

Abstract: Lung cancer is the leading disease of cancer-related deaths worldwide. Since the beginning of the 20th century, various infectious agents associated with lung cancer have been identified. The mechanisms that include systemic inflammatory pathways as effect of microbial persistence in the lung can secondarily promote the development of lung carcinogenesis. Chronic inflammation associated with lung-cancer infections is known to precede tumor development, and it has a strong effect on the response(s) to therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 138 publications
0
36
0
1
Order By: Relevance
“…Links between infection, inflammation and lung cancer has been fully defined and the mechanism has been established that systemic inflammatory pathways as effect of microbial persistence in the lung can secondarily promote the development of lung carcinogenesis ( 26 ). In the present study, we showed that patients with LUSC have more frequent cough, fever, microbial infection and larger number of leukocytes than that in patients with LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…Links between infection, inflammation and lung cancer has been fully defined and the mechanism has been established that systemic inflammatory pathways as effect of microbial persistence in the lung can secondarily promote the development of lung carcinogenesis ( 26 ). In the present study, we showed that patients with LUSC have more frequent cough, fever, microbial infection and larger number of leukocytes than that in patients with LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer seriously affects the survival and life of patients, especially lung cancer (LC), which is the main contributor to global cancer mortality, causing more than 700,000 deaths every year ( 1 ). Recent research shows that cancer is closely related to autoimmunity, and immunotherapy as a new treatment method has received extensive attention in the field of cancer therapy ( 2 ). Immune infiltration in the tumor microenvironment (TME) is the basis of immunotherapy and plays a key role in tumorigenesis and development and also affects the clinical prognosis of patients ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…This complex metabolic disorder has recently emerged as one of the main contributing factors to HCC development. The link between human cancer and viral infections has already been well documented [ 15 , 16 ]. However, although cirrhosis and chronic hepatitis B infection remain the main risk factors linked with HCC (in 50% of all cases), a growing amount of clinical evidence suggests that approximately 24% of the HCC cases are a consequence of neglected NAFLD [ 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%